MELAMPAUI AGILITAS: PERAN AMBIDEKSTERITAS INOVASI DALAM MENDORONG PERTUMBUHAN SKALABEL BISNIS STARTUP SAAS - Nugroho, Robertus Adi; Sepungan, Maria Indah Lestari (Catholic University Musi Charitas, 2026)
Purpose: This study aims to examine how strategic agility contributes to startup scalability through innovation ambidexterity, comprising exploration and exploitation, in Software as a Service startups. Although strategic agility has been widely recognized as a critical capability in dynamic environments, limited empirical evidence explains how it is translated into scalable growth, particularly within emerging digital ecosystems. Design Methodology Approach: A quantitative approach was employed using a survey method. Data were collected from strategic decision makers in SaaS startups operating in Jakarta and Surabaya. The proposed research model was analyzed using Partial Least Squares Structural Equation Modeling to assess direct, indirect, and mediation effects among the constructs. Findings: The results indicate that strategic agility does not have a significant direct effect on startup scalability. However, strategic agility significantly influences both dimensions of innovation ambidexterity. Exploration demonstrates a strong and positive effect on startup scalability, whereas exploitation shows a non-significant relationship. Further analysis reveals that exploration fully mediates the relationship between strategic agility and startup scalability, while exploitation does not serve as a mediating mechanism. Practical Implications: The findings suggest that SaaS startups should not rely solely on strategic agility to achieve scalable growth. Instead, agility needs to be effectively translated into exploratory innovation activities, such as experimentation, new feature development, and market exploration. While exploitation remains important for operational efficiency, its role in driving scalability appears limited at early growth stages. Originality Value: This study provides empirical evidence that exploration functions as a full mediating mechanism linking strategic agility to startup scalability. The findings extend Dynamic Capability Theory by clarifying how higher-order capabilities are translated into growth outcomes through innovation processes. Additionally, the study highlights the asymmetric roles of exploration and exploitation within the context of SaaS startups in emerging markets.